ISLAM DAN PARTISIPASI POLITIK PEREMPUAN: Analisis Normatif dan Historis - Purnomo, Agus (Pusat Studi Gender UIN Maulana Malik Ibrahim Malang, 2008)
Normatively, Islam gives equal access for men and women to participate in public arena. Historical reality notes in the historiography of Islam also presenting impressing